miR-618 Inhibits Prostate Cancer Migration and Invasion by Targeting FOXP2 - Song, Xian-Lu (J Cancer, 2017)
miRNAs play critical role in the development and progression of prostate cancer. Here we studied the role of miR-618 in prostate cancer migration and invasion. miR-618 was downregulated in metastatic androgen-independent prostate cancer (AIPC), patients with low miR-618 had poor outcome. Overexpression of miR-618 inhibited migration and invasion and induced mesenchymal to epithelial transition (MET). Conversely, knockdown of miR-618 promoted migration and invasion and induced epithelial to mesenchymal transition (EMT). FOXP2 was the direct target of miR-618, and promoted TGF-β expression, inhibition of TGF-β reversed the effect of miR-618 knockdown. We further analyzed the correlation between miR-618 expression and FOXP2 in human prostate cancer tissues, and found there was a negative correlation between miR-618 expression and FOXP2 levels. In conclusion, we found miR-618 inhibited prostate cancer migration and invasion by targeting FOXP2 and inhibiting TGF-β.